Oral Anticoagulants in Low-Risk Atrial Fibrillation Patients: A Population-Based Study - Denas, Gentian; Gennaro, Nicola; Ferroni, Eliana; Fedeli, Ugo; Zoppellaro, Giacomo; Corti, Maria Chiara; Pengo, Vittorio (Cardiology and Cardiovascular Medicine, 2020)
Aim: The use of oral anticoagulant drugs in patients with atrial fibrillation and one non-gender related risk factors is challenging. We compared the efficacy and safety of DOACs vs VKAs in low risk patients. Methods: We performed a population-based retrospective cohort study in anticoagulation-naïve atrial fibrillation patients. The cohort was identified, characterized and followed-up using data from administrative claims, drug prescriptions archive, and regional inpatient and discharge register. Event-rates were assessed using as treated analysis. Hazard ratios (HR) of stroke and major bleeding were estimated by Cox regression analysis. Results: Overall, we identified 1829 patients treated with DOACs and 6083 patients treated with VKAs, that accumulated 2097 and 4681 person-years of follow up, respectively. Half of patients were in the 65-75 age group, while almost 38% were female. Stroke rates were lower with DOACs as compared to VKAs: 0.14% person-years versus 0.28% person-years (HR 0.50, 95%CI 0.14–1.74). Major bleeding (0.81% person-years versus 1.09% person-years (HR 0.80, 95%CI 0.46–1.40)) and intracranial hemorrhage (0.33% person-years versus 0.42% person-years (HR 0.85, 95%CI 0.36–2.04) were also lower with DOACs. Mortality rate with DOACs was 1.2% person-years and 1.1 person-years with VKA (HR 1.21, 95%CI 0.74-1.96) mostly driven by death from cancer in the DOACs group. Conclusions: In low risk patients with atrial fibrillation, there is a benefit (although non-significant) with DOACs as compared to VKAs. Other studies are required to directly test this finding.